Home improvement. The complete third season [videorecording (DVD)] - Allen, Tim, 1953-; Richardson, Patricia, 1951-; Hindman, Earl, 1942-2003; Thomas, Jonathan Taylor; Bryan, Zachery Ty; Smith, Taran Noah, 1984-; Karn, Richard (ABC Studios, 2015)
Sitcom revolving around Tim "The Tool Man" Taylor who has his own television show "Tool Time" and his family. Season five contains episodes in which Tim lets an honorary degree go to his head, Jill's success in school leads her to begin doling out psychiatric "help", and Tim must make a stand when his new boss tries to replace Al.